2017
DOI: 10.1038/srep45684
|View full text |Cite
|
Sign up to set email alerts
|

Action potential initiation in a two-compartment model of pyramidal neuron mediated by dendritic Ca2+ spike

Abstract: Dendritic Ca2+ spike endows cortical pyramidal cell with powerful ability of synaptic integration, which is critical for neuronal computation. Here we propose a two-compartment conductance-based model to investigate how the Ca2+ activity of apical dendrite participates in the action potential (AP) initiation to affect the firing properties of pyramidal neurons. We have shown that the apical input with sufficient intensity triggers a dendritic Ca2+ spike, which significantly boosts dendritic inputs as it propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…It is also well matched to the performance of a two 'compartment' model (e.g. Figure 5b of [32]) which shows that apical amplification depends strongly on calcium conductance in the apical trunk.…”
Section: Dependence Of Second Ap Probability On Apical and Basal Inputsupporting
confidence: 58%
“…It is also well matched to the performance of a two 'compartment' model (e.g. Figure 5b of [32]) which shows that apical amplification depends strongly on calcium conductance in the apical trunk.…”
Section: Dependence Of Second Ap Probability On Apical and Basal Inputsupporting
confidence: 58%
“…However, such a quantitative approach is very challenging if biophysical models are used to simultaneously fit data from multiple experimental paradigms. In such cases, a qualitative trial/error approach based on electrophysiological knowledge about the effect that each ion channel produces on the data are more effective (Schaefer et al, 2003;Larkum et al, 2004;Yi et al, 2017). We will use the qualitative trial/error approach as a satisfying strategy to reproduce the six features of L5-PCs observed in various experimental paradigms (Table 3) without a meticulous quantitative description of the Na 1 -APs and Ca 21 spikes.…”
Section: Model Testing Approachmentioning
confidence: 99%
“…Previous simplified biophysical models explained some key features, that is, the I-f curves (Larkum et al, 2004) and the backpropagating AP-activated Ca 21 spike (BAC) firing (Chua et al, 2015;Yi et al, 2017). More complex biophysical models accounted for some combinations of the three major features: the BAC firing (Rapp et al, 1996;Schaefer et al, 2003;Hay et al, 2011;Bahl et al, 2012;Almog and Korngreen, 2014;Mäki-Marttunen et al, 2018), the f-I curves (Hay et al, 2011;Bahl et al, 2012;Mäki-Marttunen et al, 2018), and the CF of Ca 21 spikes (Schaefer et al, 2003;Hay et al, 2011;Bahl et al, 2012;Almog and Korngreen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have observed that dendritic Ca 2+ spike triggers a burst of APs in the soma/axon and switches the firing mode of the cell to bursting (Williams and Stuart, 1999 ; Larkum and Zhu, 2002 ; Larkum et al, 2004 ; Palmer et al, 2012 ; Larkum, 2013 ). With a two-compartment model, our earlier study (Yi et al, 2017 ) has successfully reproduced this observation and explained how dendritic spike participates in somatic AP initiation. In present study, we show that the activation of Ca 2+ current in apical dendrites makes Na + entry become efficiently used by APs for their depolarization, thus facilitating the effective utilization of metabolic energy.…”
Section: Discussionmentioning
confidence: 58%
“…Two-compartment model is the minimal neuronal unit for capturing the interaction between dendrites and soma/axon, which has been widely used to describe the input-output transfer of single pyramidal cell. In particular, our earlier studies (Yi et al, 2014a , b , 2015b , 2016b , 2017 ) have demonstrated that dendrite area, dendritic spike and coupling conductance all play crucial roles in determining the transfer function of two-compartment model neurons. For example, they could alter the dynamic basis of spike initiation (Yi et al, 2014a , 2017 ), the outcome of subthreshold competition between opposite currents (Yi et al, 2014a , b , 2015b ), the dynamics of AP threshold (Yi et al, 2016b ), the electric field threshold for triggering spikes (Yi et al, 2014b ), and the field-induced SFA (Yi et al, 2015b ).…”
Section: Discussionmentioning
confidence: 99%